(untitled) - Waterhouse, D. F. (Canberra, 1998)
The present volume is a companion to biological control of weeds: Southeast Asian Propects (Waterhouse 1994). It summaries what is known about the natural enemies (principally the parasitoids) of the major exotic insect pests and indicates propects
Keywords: Insect pests,Insect pests,Arthropod pests; Biological control,Control,Biological control; Southeast Asia